(untitled) (International Journal of Agricultural Extension and Education, 2025)
This paper investigates farmers’ intentions toward adopting organic farming practices and the associated challenges they encounter. Through a combination of surveys, interviews, and field observations, the study reveals a notable interest among farmers in transitioning to organic farming but identifies significant barriers that prevent this shift. Key challenges include limited availability and high costs of organic inputs, inadequate technical support, and financial constraints. The findings highlight the urgent need for policy interventions to address these issues effectively. Recommendations for policymakers include improving access to affordable organic inputs, expanding educational and technical support programs, and implementing financial assistance schemes to alleviate initial investment burdens. By addressing these challenges, policymakers can facilitate a smoother transition to organic farming, supporting farmers in their pursuit of sustainable agricultural practices and contributing to the overall resilience and sustainability of the agricultural sector.